Examination of degenerative and damaged glenohumeral joint tissue samples with calorimetric analyses - Lőrinczy, Dénes; Bata, András; Bogdán, László; Pillér, Árpád; Nöt, Laszlo G. (Frontiers in Cell and Developmental Biology, 2025)
Introduction: In recent decades, the operative treatment of degenerative changes of large joints has undergone significant changes. Similarly, new surgical methods have become available for the treatment of fractures affecting the joint surface. Despite the development of medical imaging procedures, it is still a challenge to accurately assess the state of the joints prior to surgery. Our workgroup has widely used differential scanning calorimetric analyses (DSC) for the evaluation of different human anatomical structures. Aims: The purpose of the study was to find a potential relationship between the calorimetric changes of human glenohumeral tissue samples and the results of medical imaging, macroscopical and histological examinations. Patients and methods: various type of tissue samples (rotator cuff tendon, hyaline cartilage and subchondral bone of the humeral head) was collected from patients underwent reversed shoulder arthroplasty with indication of rotator cuff tear arthropathy or Neer Type VI proximal humerus fractures. CT and MRI examinations were performed prior to surgery. Thermal parameters were detected using differential scanning calorimetry (DSC) and thermogravimetry (DTA/TG). Intraoperative macroscopic analysis and histology were done to confirm our findings. Results: we have demonstrated that thermal parameters and denaturation curves of different types of tissue samples followed the results of preoperative CT or MRI examinations, macroscopic findings and histological analyzes. These findings were supported by regression analysis, using score systems for radiological and other changes. Conclusion: our data suggest that the calorimetric analysis of intraoperatively collected tissue samples could be a reliable method for the clinical investigation of damaged (fractured) or degenerative joints.